An Admissible Asymptotic-Preserving Numerical Scheme for the Electronic $M_1$ Model in the Diffusive Limit (Communications in Computational Physics, 2018)
This work is devoted to the derivation of an admissible asymptotic-preservingscheme for the electronic $M_1$ model in the diffusive regime. A numerical scheme isproposed in order to deal with the mixed derivatives which arise in the diffusive limitleading to an anisotropic diffusion. The derived numerical scheme preserves the realisabilitydomain and enjoys asymptotic-preserving properties correctly handling thediffusive limit recovering the relevant limit equation. In addition, the cases of nonconstants electric field and collisional parameter are naturally taken into account withthe present approach. Numerical test cases validate the considered scheme in the non-collisionaland diffusive limits.